Systemic Candesartan Treatment Modulates Behavior, Synaptic Protein Levels, and Neuroinflammation in Female Mice That Express Human APOE4 - Scheinman, Sarah B.; Zaldua, Steve; Dada, Adedoyin; Krochmaliuk, Kateryna; Dye, Katherine; Marottoli, Felecia M.; Thatcher, Gregory R. J.; Tai, Leon M. (Frontiers in Neuroscience, 2021)
Evidence suggests that angiotensin receptor blockers (ARBs) could be beneficial for Alzheimer’s disease (AD) patients independent of any effects on hypertension. However, studies in rodent models directly testing the activity of ARB treatment on behavior and AD-relevent pathology including neuroinflammation, Aβ levels, and cerebrovascular function, have produced mixed results. APOE4 is a major genetic risk factor for AD and has been linked to many of the same functions as those purported to be modulated by ARB treatment. Therefore, evaluating the effects of ARB treatment on behavior and AD-relevant pathology in mice that express human APOE4 could provide important information on whether to further develop ARBs for AD therapy. In this study, we treated female and male mice that express the human APOE4 gene in the absence (E4FAD-) or presence (E4FAD+) of high Aβ levels with the ARB prodrug candesartan cilexetil for a duration of 4 months. Compared to vehicle, candesartan treatment resulted in greater memory-relevant behavior and higher hippocampal presynaptic protein levels in female, but not male, E4FAD- and E4FAD+ mice. The beneficial effects of candesartan in female E4FAD- and E4FAD+ mice occurred in tandem with lower GFAP and Iba1 levels in the hippocampus, whereas there were no effects on markers of cerebrovascular function and Aβ levels. Collectively, these data imply that the effects of ARBs on AD-relevant pathology may be modulated in part by the interaction between APOE genotype and biological sex. Thus, the further development of ARBs could provide therapeutic options for targeting neuroinflammation in female APOE4 carriers.